Azithromycin: The first broad-spectrum therapeutic (2020)
The Strategic Plan for Biodefense Research by the U.S. Department of Health and Human Services demarcates the need for drugs which target multiple types of pathogens to prepare for infectious threats. Azithromycin is one such broad-spectrum therapeutic that is both included in the University of Oxford’s RECOVERY and excluded from the World Health Organization’s SOLIDARITY trials. Here we review azithromycin’s broad antibiotic, antimalarial, antiviral pharmacology and contextualise it against a broader history as the most repositioned therapeutic of the macrolide class; we further evaluate azithromycin’s clinical and socio-economic propriety for respiratory pandemics and delineate a model for its combinatorial mechanism of action against COVID-19 pneumonia.